Turkish media coverage of children's relation to the digital world: From moral panic to the recognition of opportunities and rights - Bilgic, Esra Ercan (Sage Publications Inc, 2024)
UN General Comment No. 25 (2021) emphasizes the importance of safeguarding children's rights in the digital sphere. However, in Turkey, media coverage often focuses on the negative aspects of the relationship between digital media and children, overshadowing opportunities, and rights. This study aims to analyze news articles focused on digital media and children to address this issue. Key concepts such as moral panic, framing and discourse are incorporated. Initially assuming a perception of digital media as a threat to social norms and children's interests, the study utilizes a discourse-historical approach (DHA) to contextualize and explore the discursive strategies employed by national daily newspapers. Conducting a cross-sectional study, textual data from national dailies between January 1, 2015 and January 1, 2020, in Turkey are collected, resulting in a corpus of 187 news articles. These articles undergo discourse historical analysis guided by the research question: How is children's relationship with the digital world portrayed and discussed in public discourse? The findings reveal a predominant focus on risks over opportunities and rights, contributing to moral panic and impeding children's civic participation. In conclusion, this study advocates for the adoption of a child rights perspective in Turkish newspapers to better serve the interests of children.
Keywords: Children'S Civic Participation; Children'S Digital Rights; Discourse Analysis; Moral Panic; Turkish Media Coverage